Atomically Thin Quantum Spin Hall Insulators. Issue 22 (23rd April 2021) - Lodge, Michael S.; Yang, Shengyuan A.; Mukherjee, Shantanu; Weber, Bent
Abstract: Atomically thin topological materials are attracting growing attention for their potential to radically transform classical and quantum electronic device concepts. Among them is the quantum spin Hall (QSH) insulator—a 2D state of matter that arises from interplay of topological band inversion and strong spin–orbit coupling, with large tunable bulk bandgaps up to 800 meV and gapless, 1D edge states. Reviewing recent advances in materials science and engineering alongside theoretical description, the QSH materials library is surveyed with focus on the prospects for QSH‐based device applications. In particular, theoretical predictions of nontrivial superconducting pairing in the QSH state toward Majorana‐based topological quantum computing are discussed, which are the next frontier in QSH materials research. Abstract : Atomically thin quantum spin Hall (QSH) insulators—a class of 2D topological insulators—promises to radically transform classical and quantum electronic device concepts. Advances in materials science and engineering are surveyed, alongside a theoretical description, and the future perspectives for electronic applications are discussed, including the quest to realizing Majorana‐based topological quantum computing—the next frontier in QSH materials research.